Stress around perforation - Samsuri, Ariffin (Faculty of Chemical and Natural Resources Engineering, 1991)
This paper presents the results of a study into the stress around the perforation system. Finite element models of the main factors associated with a borehole and perforations were generated and subjected to various load regimes. The results show the effects of main parameters on the overall stress around the perforation system.